Study on Epoxy Resin-Modified Asphalt Binders with Improved Low-Temperature Performance - Zhiqi Luo; Tao Liu; Yintan Wu; Hongwei Yuan; Guoping Qian; Xiantao Meng; Jun Cai (Advances in Civil Engineering)
Epoxy resin-modified asphalt binder (ERMAB) has been wildly used in the pavement of steel bridges, while the improvement on its low temperature is still a big challenge to researchers. This paper tries to improve the low-temperature performance of ERMAB by optimizing the modifier, epoxy resin. Firstly, three epoxy resins and three amine curing agents were prepared and used for the modification of asphalt binders. Secondly, the formula and prepared methods of ERMABs were optimized and determined through compatibility, viscosity growth rate, and tensile tests. Thirdly, an overall comparison on the phase structure, thermal stability, low-temperature performance, temperature and frequency dependence, and fatigue performance of prepared ERMABs and control sample were made. Results show that polyurethane-modified epoxy resin or dimer acid-modified epoxy resin, with a suitable curing agent, can significantly improve the low-temperature performance of ERMAB, and the curing time meets the construction requirements. Compared with the control sample, the two ERMABs have basically the same rheological properties at medium temperature, but slightly worse high-temperature performance and fatigue resistance. The significance of this paper lies in proposing a feasible way to improve the low-temperature performance of ERMAB.